The Role of Multidisciplinary Rehabilitation in Enhancing Comprehensive Cancer Care: A Descriptive Review - Rathore, Farooq Azam; Arshad, Sana; Haris Mumtaz Malik (Journal of University College of Medicine and Dentistry, 2024)
Objective: This review aims to highlight the effectiveness of various forms of cancer rehabilitation in improving physical, emotional, and social outcomes for patients with cancer. It evaluates the impact of cancer rehabilitation on physical function, psychological health, and social reintegration while identifying barriers and facilitators in the implementation of cancer rehabilitation programs. Methods: A literature search was conducted from December 2023 to February 2024, using two electronic databases: MEDLINE (via PubMed) and Google Scholar. After screening the titles and abstracts, the study selected 34 articles, including RCTs, clinical trials, observational studies, and systematic reviews. The study did not include letters to the editor, editorials, special and short communications, animal-based research, and non-English language publications. There were no restrictions on geographical distribution, age of the sample population, type, severity, duration, and outcome of cancer, or the year range from which the studies were selected. Results: Rehabilitation interventions were effective in different cancer types, including breast, prostate, lung, and colorectal cancers. These interventions addressed common treatment-related challenges such as fatigue, pain, lymphedema, incontinence, and psychological issues, improving patients’ quality of life and physical functioning. However, challenges such as physical limitations, emotional distress, access to care, financial barriers, and coordination of services were frequently noted. This highlights the need for tailored, accessible, and well-coordinated rehabilitation programs. Conclusion: Multidisciplinary and coordinated cancer rehabilitation has the potential to improve mobility, quality of life and physical functioning across various cancer types, but challenges in accessibility and coordination must be addressed.